2014
DOI: 10.1016/j.fob.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal nuclease domain containing‐1 (SND1) promotes migration and invasion via angiotensin II type 1 receptor (AT1R) and TGFβ signaling

Abstract: HighlightsSND1 augments AT1R receptor level by posttranscriptional regulation.SND1 activates TGFβ signaling which promotes the epithelial–mesenchymal transition.Migration and invasion by human hepatocellular carcinoma (HCC) cells are augmented by SND1.A correlation is observed between SND1 and AT1R expression in HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 32 publications
2
56
0
Order By: Relevance
“…Other tumor-associated genes found to be mutated as single events in individual tumors in the SCOs within our cohort include FAT atypical cadherin 1 ( FAT1 ) [15], staphylococcal nuclease domain-containing protein 1 ( SND1 ) [16, 17], Cbl proto-oncogene E3 ubiquitin protein ligase ( CBL ), frizzled class receptor 7 ( FZD7 ), phosphatidylinositol-4,5-bisphosphate 3-kinase subunit gamma ( PIK3CG ), and SH3 domain binding kinase 1 ( SBK1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other tumor-associated genes found to be mutated as single events in individual tumors in the SCOs within our cohort include FAT atypical cadherin 1 ( FAT1 ) [15], staphylococcal nuclease domain-containing protein 1 ( SND1 ) [16, 17], Cbl proto-oncogene E3 ubiquitin protein ligase ( CBL ), frizzled class receptor 7 ( FZD7 ), phosphatidylinositol-4,5-bisphosphate 3-kinase subunit gamma ( PIK3CG ), and SH3 domain binding kinase 1 ( SBK1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Case 2 contained a mutation in SND1 , which has been reported to be involved in glioblastoma and carcinomas of the colon, prostate, and liver [16, 1820]. SND1 is a component of the RNA-induced silencing complex (RISC) and has been reported to activate the MAP kinase ERK [17]. Case 1 contained a mutation in the tumor suppressor FAT1 atypical cadherin gene, which has been implicated in glioblastoma, colorectal adenocarcinoma, and head and neck squamous cell carcinoma [15].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation is a critical event in HCC pathogenesis and induction by inflammatory cytokines might underlie the overexpression of SND1 in human HCC patients. Overexpression and knockdown studies in human HCC cells have demonstrated that SND1 promotes proliferation, migration, invasion and in vivo tumorigenesis [38][39][40][41] . As a component of the RISC in HCC cells, SND1 promotes oncogenic miRNA-mediated degradation of tumor suppressor mRNAs [38] [ Figure 2].…”
Section: Snd1 As An Oncogene For Hccmentioning
confidence: 99%
“…However, when overexpressed, SND1 could significantly augment RISC activity in human HCC cells when compared to normal hepatocytes [38] . By binding to and stabilizing angiotensin II type 1 receptor (AT1R) mRNA, SND1 activates TGFb and ERK signaling, thereby promoting epithelial-mesenchymal transition (EMT), in vitro migration and invasion by HCC cells [39] . In HCC cells, SND1 activates NF-κB, resulting in induction of miR-221 and angiogenic factors angiogenin and CXCL16 that promote tumor angiogenesis [40] .…”
Section: Snd1 As An Oncogene For Hccmentioning
confidence: 99%
“…This gene was first cloned by Yanaka et al, both in human and mouse [78, 79]. The expression of NPR-C is also ubiquitous and is known to be expressed in heart, lung, adrenal gland, heart, cerebral cortex, cerebellum, liver and adipocytes and in some cancers [80, 81]. The expression of NPR-C is influenced by various physiological factors and is reported to be very high in hypertensive, diabetic and obese patients [80].…”
Section: Natriuretic Peptide Receptorsmentioning
confidence: 99%